2022
DOI: 10.1007/s11259-022-10052-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bovine uterine fluid extracellular vesicles proteomic profiles at follicular and luteal phases of the oestrous cycle

Abstract: Extracellular vesicles (EV) have been identified in uterine fluid (UF), however the bovine UF-EV profile during different phases of the oestrous cycle has not yet been established. Therefore, we compared the UF-EV, and their protein profile at follicular and luteal phases of the oestrous cycle. UF samples were collected from healthy uteri of six live and six slaughtered cows at follicular or luteal phases. Isolation of EV was performed using tangential flow filtration followed by size exclusion chromatography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In one of our previous studies, we have identified 2587 proteins in the UF-EVs enriched from cows with natural cycle, where 41 proteins were differentially expressed between follicular and luteal phases of the estrous cycle ( 13 ). When comparing the results of present study of UF-EV proteome acquired from synchronized cows and the previous UF-EV proteome study from naturally cyclic cows, we identified that 51.7% of proteins were overlapping in both datasets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one of our previous studies, we have identified 2587 proteins in the UF-EVs enriched from cows with natural cycle, where 41 proteins were differentially expressed between follicular and luteal phases of the estrous cycle ( 13 ). When comparing the results of present study of UF-EV proteome acquired from synchronized cows and the previous UF-EV proteome study from naturally cyclic cows, we identified that 51.7% of proteins were overlapping in both datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, 500 μl of sample was added on top of the filter in the column. Immediately after adding the sample, 500 μl fractions were collected from which fraction 6 to 9 contained EVs ( 13 ). Fractions 6 to 9 were pooled and further concentrated up to 500 μl using Amicon Ultra-2 ml centrifugal filters (10 kDa cut-off, Merck Millipore Ltd) by centrifuging at 4 °C at 2000 g. Enriched EV samples were stored at −80 °C in protein low-binding tubes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes have become a focal point in biomedical research due to their crucial influence on various biological functions and their ability to modulate microenvironments 21,22 . Exosomes, classified as membrane-bound nanovesicles with sizes ranging from 30 to 200 nm 23 , are released from diverse cell types and bodily fluids, including blood 24 , saliva 25 , breast milk 26 , urine 27 , tears 28 , and vaginal discharge 29 . These small vesicles transport bioactive compounds like proteins, nucleic acids, and lipids 30,31 .…”
Section: Mainmentioning
confidence: 99%
“…ENPP6 exists in two forms: a glycosylphosphatidylinositol (GDI)-anchored enzyme and, after cleavage of the GDI-anchor, a soluble enzyme. However, ENPP6 is predominantly expressed in the brain and kidney (Greiner-Tollersrud, 2014), although it has been detected in bovine uterine fluids (Piibor et al, 2023). Glycerophosphodiester phosphodiesterase domain containing 5 (GDPD5) is widely expressed in humans, including in the uterus, and can also generate choline from GPC (Gallazzini et al, 2008;Lang et al, 2008).…”
Section: Pap Liberates Choline From Seminal Gland-secreted Phosphocho...mentioning
confidence: 99%